Lower Urinary Tract Symptoms and Efficacy of Anticholinergic Drugs in Patients Remaining Disease-Free After Radical Retropubic Prostatectomy - Yang, Seung Woo; Na, Yong Gil; Song, Ki Hak; Shin, Ju Hyun; Chang, Young Seop; Park, Jong Mok; Lee, Chung Lyul; Lim, Jae Sung (Urology Journal, 2016)
Purpose: This study was conducted to evaluate lower urinary tract symptoms (LUTS) change in patients with localized prostate cancer after radical retropubic prostatectomy (RRP) and examine the efficacy of anticholinergic drugs to treat patients suffering from storage symptoms. Materials and Methods: Among 50 patients who underwent RRP for prostate cancer, 40 who did not undergo additional treatment that might affect their urination pattern were included in the analysis. The International Prostate Symptom Score (IPSS), quality of life (QoL) score, and uroflowmetry were analyzed prior to RRP and 12 months after RRP. Twelve months after RRP, patients desiring improvement of storage symptoms were administered anticholinergic drugs for 6 months; the effects of such treatments were analyzed 3 and 6 months later. Results: Preoperatively and at 12 months after surgery, the mean IPSS for patients were 10.9 ± 6.7 and 9.2 ± 5.7, respectively. The mean IPSS for patients desiring improvement of storage symptoms before and after administration of medication were 9.7 ± 5.9 and 9.0 ± 4.4, respectively. In particular, the mean storage symptom composites improved significantly after administration of medication. There were no statistically significant differences in frequency between baseline and 3-month, but frequency was improved significantly after 6 months. Urgency and nocturia were improved significantly after 3 months. Conclusion: In patients undergoing RRP, urinary symptoms change over time, with worsening storage symptoms. Our results suggest that, in patients who had discomfort with storage symptoms after RRP, anticholinergic drugs significantly improved symptoms and QoL.